Material Requirement Planning of Choco Roll Product with Least Total Cost (LTC) and Least Unit Cost (LUC) Method at PT. XYZ - Marbun, Chandra Ericson; Ernawati, Dira (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
PT. XYZ is one of corporate company engaged in the snack industry. One of PT. XYZ fast moving product is Choco Roll. Choco Roll product have many forming raw material. There is around 20 raw material and packaging material to make 1 box of Choco Roll. Problem that aries at PT. XYZ is in the the supply of raw materials related to the scheduling of ordering raw materials. The company wants to store enough raw material inventory to be able to immediately fulfill all production processes, but this method is not effective and efficient because it will increase storage costs, expiration may occur, and there is a risk of price drops at any time. When a company wants to try to reduce costs by decrease the level of inventory of raw materials on hand, namely the inventory of raw materials that are already in the warehouse, but this condition will disrupt the production process if there are frequent shortages or stockouts of raw materials. Therefore to reduce the inventory cost, it needs to be make best planning in determining the number of ordered of raw material. The company must use a more scheduled raw requirements planning method to obtain a more optimal inventory cost. The purpose of this study is to determine the exact number quantity and order frequency to reduce inventory cost. This research uses lotting technique Least Total Cost (LTC) and Least Unit Cost (LUC) base on Material Requirement Planning (MRP) method. Based on the result of the Choco Roll demand from June 2022 to May 2023 obtained the total inventory cost of IDR 67,683.53 decrease by 25% to company real planning.